Sociology of Rationalism: M. Weber vs. K. Marx - Norkus, Zenonas (Problemos, 1990)
Max Weber’s sociology is interpreted as an ideal typical theory of possible solutions (rationalisation) of the universal problems of social life. History pretends by itself the process in which the possibilities are realised, when a particular solution to the problem contradicts, impedes, supposes or favours the other one. The western capitalism is the organisation of economy, which makes it possible to solve the main problem of economy, that of the optimal allocation of resources under the circumstance of scarceness. The conceptions of the genesis of capitalism, those of M. Weber and of K. Marx, are compared.